The Correlation Lifestyle with the Incidence of Diabetes Mellitus Type 2 - Erika Martining Wardani; Riezky Faisal Nugroho (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: The structure of society that changes from agrarian patterns to industrial societies contributes a lot to lifestyle changes that can trigger an increase in Non-Communicable Diseases, one of which is Diabetes Mellitus (DM). A changed lifestyle is diet and physical activity. Unhealthy diet and lack of physical activity are one of the triggers for the onset of DM type 2.Objective: To analyze the correlation between lifestyle (diet and physical activity) and the incidence of DM type 2.Methods: The design of this study is analytical observational with a retrospective study. The population of this study was all dm sufferers diagnosed with diabetes mellitus type 2 at the Waru Siodarjo Health Center. Sampling was carried out by purposive sampling, 60 samples in this study, and research instruments using questionnaire sheets. The Statistical Test used is Chi-Square.Results: Based on research that has been carried out, it was found that there was a relationship between diet (p=0.000 < α=0.05) and physical activity (p=0.001 < α=0.05) and the incidence of DM type 2.Conclusion: lifestyle relationship with the incidence of DM type 2. Nurses and nutritionists to pay more attention to diet and conduct diabetic gymnastics and for people with DM to control their diet and physical activity regularly.